Distribution of cardiac troponin I in the Japanese general population and factors influencing its concentrations. Issue 3 (1st August 2017) - Abe, Naoya; Tomita, Kenichiro; Teshima, Mayumi; Kuwabara, Maki; Sugawa, Satoshi; Hinata, Nae; Matsuura, Masaaki; Fujiwara, Mutsunori; Takaya, Kazuhiko; Hiyoshi, Toru; Uozumi, Hiroki; Ikenouchi, Hiroshi; et al.
Abstract : Background: The 99th percentile of cardiac troponin I level in the general population is accepted as the cut‐off for the diagnosis of acute myocardial infarction (AMI). However, it is not clear whether the cut‐offs derived in racially and geographically different populations are applicable in Japan. Methods: Troponin I was determined using the Abbott ARCHITECT STAT high‐sensitive troponin I immunoassay in 698 apparently healthy individuals who visited the Japanese Red Cross Medical Center for a health checkup. Results: The 99th percentile of the hsTnI in the overall population was 22.5 (95% confidence interval (CI), 16.8‐36.6) pg/mL, 17.7 (95% CI 12.0‐22.8) pg/mL for females and 30.6 (95% CI 17.1‐53.4) pg/mL for males. The median of the hsTnI in the overall population was 3.2 (95% CI, 3.0‐3.3) pg/mL, 2.6 (95% CI 2.4‐2.8) pg/mL for females and 4.0 (95% CI 3.8‐4.3) pg/mL for males. The age and gender had a significant influence on these values. The troponin I level also showed significant associations with the body mass index (BMI), the gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), estimated glomerular filtration rate (eGFR), and cardiac abnormalities by electrocardiography (ECG) but not with the high‐sensitive C‐reactive protein (hsCRP) level. Conclusions: The 99th percentiles of the troponin I measured in the general population in Japan were comparable as the ones derived in the US, Germany, and Singapore. The troponin I level was dependent on the gender, age, BMI, and cardiac abnormalities found by ECG but not by the hsCRP level.